A PCR-DGGE method for the identification of histamine-producing bacteria in cheese. (May 2016) - Diaz, Maria; Ladero, Victor; Redruello, Begoña; Sanchez-Llana, Esther; del Rio, Beatriz; Fernandez, Maria; Martin, Maria Cruz; Alvarez, Miguel A.
Abstract: Histamine is the biogenic amine (BA) most frequently involved in food poisoning. Cheese is among the foods in which it is most commonly found, and in some of the highest concentrations. Its accumulation in cheese is mainly due to the presence of lactic acid bacteria (LAB) that produce histidine decarboxylase, an enzyme coded by the gene hdcA . This gene has been sequenced in several histamine-producing LAB. This paper reports a new culture-independent method based on PCR-DGGE for detecting and identifying, at the species level, the histaminogenic bacteria present in cheese. Primers were designed based on the hdcA gene sequences available for Gram positive bacteria, and PCR and DGGE optimized in order to differentiate between amplicons corresponding to different histamine-producing species. The proposed method provides a rapid and simple means of detecting and identifying histamine-producing Gram positive bacteria in foods with complex microbial communities, such as cheese. Highlights: New PCR-DGGE method identifies histamine-producing bacteria at species level. The method was validated using samples of different cheese types. New species were identified as potential histamine producers in cheese. The dominant histamine-producing species in cheese is Lactobacillus parabuchneri .